Hijos naturales nacidos en tres poblados de la región oriental del estado de Tlaxcala (1889-1892) - Bernal Felipe, Natalia; Alfaro Castro, Martha E. (Estudios de Antropología Biológica, 2010)
In this work, a study about “natural children” is presented, those children that were born between 1889 and 1892, to know the frequency and conditions under this type of births were presented in the region, focusing in the analysis of the anthropological meanings of free union and social consequences for those couples who didn’t married and had children. The historical demographic tools were used to analyze 515 baptism registers from Santiago’s parochial file of Tetla, municipality of Apizaco, Tlaxcala, which housed three small villages: Santiago Tetla, Santa María Texcalac and Piedras Negras.